A cryptic targeting signal creates a mitochondrial FEN1 isoform with tailed R-Loop binding properties. - Lawrence Kazak; Aurelio Reyes; Jiuya He; Stuart R Wood; Gloria Brea-Calvo; Torgeir T Holen; Ian J Holt (PLoS ONE)
A growing number of DNA transacting proteins is found in the nucleus and in mitochondria, including the DNA repair and replication protein Flap endonuclease 1, FEN1. Here we show a truncated FEN1 isoform is generated by alternative translation initiation, exposing a mitochondrial targeting signal. The shortened form of FEN1, which we term FENMIT, localizes to mitochondria, based on import into isolated organelles, immunocytochemistry and subcellular fractionation. In vitro FENMIT binds to flap structures containing a 5' RNA flap, and prefers such substrates to single-stranded RNA. FENMIT can also bind to R-loops, and to a lesser extent to D-loops. Exposing human cells to ethidium bromide results in the generation of RNA/DNA hybrids near the origin of mitochondrial DNA replication. FENMIT is recruited to the DNA under these conditions, and is released by RNase treatment. Moreover, high levels of recombinant FENMIT expression inhibit mtDNA replication, following ethidium bromide treatment. These findings suggest FENMIT interacts with RNA/DNA hybrids in mitochondrial DNA, such as those found at the origin of replication.